Citizen Participation, Transparency, and Public Trust in Government: Participatory Budgeting in Local Governments of Korea - Soonhee Kim (Korea Development Institute (KDI), 2014)
The purpose of this book is to develop an integrated evaluation model of the success factors of effective participatory budgeting and understand the impacts of effective participatory budgeting on transparency and public trust in government in the context of the Republic of Korea. Testing the research propositions developed in the book would enhance the knowledge of what specific factors of individual, managerial, institutional, political, and cultural dimensions are relatively more significant than the others for implementing effective participatory budgeting in local governments of Korea. Drawing on a comprehensive literature review on antecedents of transparency and public trust in government, the book also offers a participatory budgeting model of transparency and public trust in government by emphasizing the roles of community values as mediator.
Keywords: 330